Shaping the EU investment regime: choice of forum and applicable law in international investment agreements - Pascual Vives, Francisco J. (CUADERNOS DE DERECHO TRANSNACIONAL, 2014)
Abstract: The paper examines the interplay between European Union Law and the internationalforeign investment protection regime. While the European institutions and its Member States shape the content of the future investment agreements and define the investment policy, it is worth analyzing in light of recent practice the eventual participation formulas of the European Union in investment arbitration, and the consideration of European Union Law as applicable Law in investment arbitration. Key words: European investment regime; Applicable Law to investment arbitration; Participation of the European Union in investment arbitration; Bilateral Investment Treaties; International Centre for Settlement of Investment Disputes; European Court of Justice; self-contained regimes; principle of systemic integration. Resumen: El trabajo examina la interacción entre el Derecho de la Unión Europea y el régimen internacional de protección de las inversiones exteriores. Mientras las instituciones de la UniónEuropea y sus Estados miembros modelan el contenido de los futuros acuerdos europeos de inversión y definen el alcance de la política europea de inversiones, es importante analizar a la luz de la práctica más reciente, las posibles fórmulas de participación de la Unión Europea en el arbitraje de inversiones y la consideración del Derecho de la Unión Europea como derecho aplicable en el arbitraje de inversiones. Palabras clave: Régimen europeo de inversiones; Derecho aplicable al arbitraje de inversiones; Participación de la Unión Europea en el arbitraje de inversiones; Tratados bilaterales de inversión; Centro Internacional para el Arreglo de Diferencias relativas a Inversiones; Tribunal de Justicia de la Unión Europea; regímenes autónomos; principio de integración sistémica..